Kajian TerapanElemen Interior Ruang Pre-Schoolpada Angels n I Children Day Care di Surabaya - Fransisca Hindiarto; Andereas Pandu Setiawan; Grace Setiati Kattu (Intra, 2015)
One of the many ways to improve the quality of Human Resource is to also improve our education quality. Children Day Care is a form of non-formal pre-school program with the basis focusing to physical and mental development such as character, behaviour, knowledge, soft skills, and creativity to provide the child enough provision to succeed later in life. The day care also function as a second family and home for a certain time in a day where parents have to work. The goal of the research is to gain data and descriptions of the applied interior elements in Angels 'n I Children Day Care & Learning Center Surabaya whether they suits the needs to optimize the children growth and development or not. The outcome of the research shows that the applied interior elements are enough to and suits the need to support the childrens growth.